Optimalisasi Peningkatan Kinerja Perangkat Daerah Dalam Perspektif Kualitas Sumber Daya Aparatur - Iwan Satibi (PUBLICA, 2011)
The improvement of government apparatus performance is a non-negotiable compulsory. The urgency of this performance improvement can be understood in tine with the increasing demands for a service of government officials that has been assessed by many experts and the result is still disappointing. One of the strategic efforts that can be done is through improving the quality of personnel resources. Therefore, the extent to which the strengthening of the policy of increasing the quality of personnel resources can make a significant contribution towards the improvement of the performance of regional-unit organization.